The COVID-19 outbreak: an update on the SARS-CoV-2 virus - Baric, Ralph (Henry Stewart Talks, 2020)
Mortality rates of SARS-CoV-2 and known risk factors, Provenance of SARS-CoV-2 and related viruses, SARS-CoV-2 as compared with seasonal influenza, Potential impact of future mutations, Prospective therapies